The bright future of nanotechnology in lymphatic system imaging and imaging-guided surgery - Shaolong Qi; Xinyu Wang; Kun Chang; Wenbin Shen; Guocan Yu; Jianshi Du (Journal of Nanobiotechnology, 2022)
Abstract Lymphatic system is identified the second vascular system after the blood circulation in mammalian species, however the research on lymphatic system has long been hampered by the lack of comprehensive imaging modality. Nanomaterials have shown the potential to enhance the quality of lymphatic imaging due to the unparalleled advantages such as the specific passive targeting and efficient co-delivery of cocktail to peripheral lymphatic system, ease molecular engineering for precise active targeting and prolonged retention in the lymphatic system of interest. Multimodal lymphatic imaging based on nanotechnology provides a complementary means to understand the kinetics of lymphoid tissues and quantify its function. In this review, we introduce the established approaches of lymphatic imaging used in clinic and summarize their strengths and weaknesses, and list the critical influence factors on lymphatic imaging. Meanwhile, the recent developments in the field of pre-clinical lymphatic imaging are discussed to shed new lights on the design of new imaging agents, the improvement of delivery methods and imaging-guided surgery strategies. Graphical Abstract